Analisis Peran Guru Dalam Menerapkan Merdeka Belajar Di SDN Meruya Selatan 04 Pagi - Ina Magdalenaa; Wilda Widiati; Darius Olak Koban (Jurnal Pendidikan, Sains Dan Teknologi, 2023)
The freedom of teachers and students is at the core of independent learning, which can create quality and international standard education. From today's point of view, teachers must reflect Pancasila-based teachings that are instilled in education today, the most important of which is love for the motherland in accordance with the contents of Pancasila itself. The meaning of independent learning includes freedom of thought, freedom of innovation, independent and creative learning, and happiness. In carrying out independent learning, it is very necessary to apply administrative management as a whole, both from the point of view of city and private administration, school principals, teachers, and the community. Educators must have a leadership role and be able to enhance school-based leadership. The Pancasila student profile is expected to be an optimal tool to encourage students to become lifelong learners who are competent, have character, and behave in accordance with Pancasila values.